Causative and Perception Constructions in European Portuguese: the dialectal data - Pereira, Sandra (2015)
This paper deals with the infinitival complements of the causative and perception verbs in European Portuguese (EP) dialects. It is based on the corpus CORDIAL-SIN (Syntax-Oriented Corpus of Portuguese Dialects – cf. http://www.clul.ul.pt/en/researcher/225-description-cordial-sin-syntax-oriented-corpus-ofportuguese- dialects) and its main goal is to describe these constructions and contrast them with the ones described for the standard EP. On one hand, the constructions identified in the standard variety, such as 1) Inflected Infinitive, 2) Exceptional Case Marking (ECM), 3) Faire-Inf and 4) Gerundial Infinitive (only for perception verbs), can be found in Portuguese dialects; by contrast, other (dialectal) non identified constructions occur in the dialectal corpus. Additionally, it is also our aim to map these different constructions in an attempt to detect some geolinguistic variation to identify syntactic areas. In what concerns the standard variety of EP, the ECM construction seems to be more common. This trend however is not confirmed by this dialectal data. Surprisingly, ECM constructions (as well as the Inflected Infinitive ones) do not show up very often and are not spread over the whole territory. Given the small amount of available data, namely for ECM construction, a parallelism between some EP varieties and other Romance languages can be suggested. In fact, it seems that this construction is not accessible in some EP varieties like it happens in the other Romance languages. In contrast, the Faire-Inf construction, which is the most frequent construction in the corpus and it is spread over the continental territory, is not found on the data from Madeira.